Practicing Radical Pedagogy: Balancing Ideals With Institutional Constraints - Sweet, Stephen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Radical pedagogy requires adopting alternative grading practices, cultivating classroom dialogue, relegating considerable power to students, and promoting social activism as part of the class expectations. An overview of, "Teaching Sociology," indicates that, probably, only a small minority of sociology teachers fully practice racial pedagogy. It is argued that college professors are free to teach racial theory, but that radical pedagogy is hindered by institutional constraints. The dramaturgical perspective is used to highlight some of the implications of different strategies radically inclined teachers may adopt in order to resolve the competing demands of their institutions amd philosophical leanings. It is concluded that radically inclined teachers and their students may benefit from balancing and tempering their commitment to radical pedagogy within the cofines imposed by their institutions.